Реалізація прокурором повноважень під час об’єднання та виділення матеріалів досудового розслідування - Шевцова, К. В.; Shevtsova, K. V. (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Юридичні науки. – 2020. – Т. 31 (70), № 4. - С. 247-251, 2020)
Розглянуто особливості реалізації повноважень прокурора під час об’єднання та виділення матеріалів досудового розслідування. Визначено законодавчі прогалини у цьому аспекті й сформовано шляхи їх усунення.

The article is devoted to the peculiarities of the exercise of the prosecutor’s powers during the merging and allocation of pre-trial investigation materials. It is emphasized that the legislative regulation of the procedure for combining and separating the materials of the pre-trial investigation is quite important both theoretically and applied. It is emphasized that interrelated actions, regardless of the presence or absence of specific legal requirements, should be investigated in a single proceeding. A large number of proposals in this regard proves the need to formulate a general rule that would determine the possible categories of such offenses. It was found that in the case of merging and separating criminal proceedings on the grounds not specified by law, these decisions should be recognized as legal, provided that there are no other violations of legal requirements and general principles of criminal proceedings. Of course, the imperfect application of legal techniques to enshrine in the CPC of Ukraine the grounds and procedure for combining and separating the materials of pre-trial investigations does not contribute to its structural and logical construction, which, in turn, complicates the application of the CPC of Ukraine. It is determined that the current legal inaccuracies and gaps in the regulation of the association and the allocation of materials for the pre-trial investigation have a negative impact on the effective implementation of the prosecutor’s authority on this issue. Moreover, in practice, this poses a threat of violation of the rights and legitimate interests of participants in criminal proceedings. Taking into account the systematic analysis of the provisions of the current CPC of Ukraine, other grounds for combining and separating the materials of the pre-trial investigation, in addition to those provided by law, have been identified. The scientific position on the broad interpretation of cases for combining the materials of the pre-trial investigation, which are not provided by the current CPC of Ukraine, has been subjected to critical analysis. The conclusion about the urgent need to improve the provisions of the current criminal procedure legislation of Ukraine in the aspect of the researched question is made

Рассмотрены особенности реализации полномочий прокурора при объединении и выделении материалов досудебного расследования. Определены законодательные пробелы в этом аспекте и сформированы пути их устранения.
Exercise of powers by the prosecutor during association and selection of materials of pre-trial investigation
Keywords: прокурор; prosecutor; досудове розслідування; pre-trial investigation; досудебное расследование; повноваження; powers; полномочия; об’єднання та виділення матеріалів; association and allocation of materials; объединение и выделение материалов